2013
DOI: 10.1111/cea.12123
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of IL‐23 and IL‐17 in a mouse model of allergic rhinitis

Abstract: IL-17 and IL-23 may play a pathogenic role in an established AR mouse model; with a more pronounced contribution of IL-23 than IL-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
4
42
1
Order By: Relevance
“…Anti-IL-23 Ab treatment significantly alleviated nasal symptoms, accompanied by reduced Th2 responses, serum OVA-specific IgE, as well as nasal neutrophil, eosinophil and mast cell infiltration (Wang et al, 2013). In this study, we found that the mRNA levels of IL-23 and IL-17 in the nasal mucosa were significantly increased in OVA-treated mice.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Anti-IL-23 Ab treatment significantly alleviated nasal symptoms, accompanied by reduced Th2 responses, serum OVA-specific IgE, as well as nasal neutrophil, eosinophil and mast cell infiltration (Wang et al, 2013). In this study, we found that the mRNA levels of IL-23 and IL-17 in the nasal mucosa were significantly increased in OVA-treated mice.…”
Section: Discussionsupporting
confidence: 53%
“…However, we found that neither IL-23 nor IL-17 was necessary for sub-mucosal thickening during chronic AR induced by OVA. Furthermore, IL-23 was reportedly produced/expressed by various types of immune cells (such as macrophages, dendritic cells and mast cells) as well as non-immune cells (such as epithelial cells, endothelial cells and fibroblasts) (Sherlock et al, 2015;Wang et al, 2013). Our findings suggest that immune-cellderived IL-23 is not essential for development of OVA-induced AR.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…[28] IL-23 is a cytokine with immunomodulatory effects. [29] It acts on memory-cluster-designation-4 (+) T cells, activates the transcription activator, and stimulates the production of interferon-gamma. [30,31] Studies showed that TH17 cells can be regulated by IL-23.…”
Section: Pediatric Osa and Inflammatory Cytokinesmentioning
confidence: 99%
“…Significantly increased IL-23p19 expression, both at messenger ribonucleic acid (mRNA) and protein levels, was demonstrated in multiple sclerotic lesions (Li http et al, 2007). Meanwhile, anti-IL-23p19 antibody is effective in treating certain autoimmune diseases (Elson et al, 2007;Cornelissen et al, 2013;Wang et al, 2013). Thus, from a therapeutic viewpoint, IL-23p19 might represent a new target for ischemic stroke therapy.…”
Section: Introductionmentioning
confidence: 99%